The second life of Tiger Woods - Bamberger, Michael, 1960- (Avid Reader Press, 2020)
Tiger Woods<U+2019>s long descent into a personal and professional hell reached bottom in the early hours of Memorial Day in 2017. Woods<U+2019>s DUI arrest that night came on the heels of a desperate spinal surgery, just weeks after he told close friends he might never play tournament golf again. His mug shot and alarming arrest video were painful to look at and, for Woods, a deep humiliation. The former paragon of discipline now found himself hopelessly lost and out of control, exposed for all the world to see. That episode could have marked the beginning of Tiger<U+2019>s end. It proved to be the opposite. Instead of sinking beneath the public disgrace of drug abuse and the private despair of a battered and ailing body, Woods embarked on the long road to redeeming himself. In The Second Life of Tiger Woods, Michael Bamberger, who has covered Woods since the golfer was an amateur, draws upon his deep network of sources inside locker rooms, caddie yards, clubhouses, fitness trailers, and back offices to tell the true and inspiring story of the legend<U+2019>s return. Packed with new information and graced by insight, Bamberger<U+2019>s story reveals how this iconic athlete clawed his way back to the top.